Cover cropping effects on olive physiology in rainfed orchards - Gonçalves, Berta C.C. (2014)
Olive orchards are often cultivated under rainfed conditions, although the irrigated areas are currently increasing. In Trás-os-Montes region, only 5% of the total area harvested is irrigated, and this picture will not change in the near future, due to natural limitation on water resources. Therefore, despite the importance of some high-density and super-high-density orchards that have been planted in the South of Portugal, it is still crucial for the olive sector, and in particular for many inland regions, that the rainfed orchards are managed in a profitable and environmentally sustainable way.